PENERAPAN PEMBELAJARAN KOOPERATIF TIPE STAD BERBASIS LESSON STUDY PADA MATA KULIAH ALJABAR LINIER - Ratih Handayani (Universitas Muhammadiyah Kotabumi, 2018)
The Implementation of STAD based lesson study on algebra subject is the problem in this research. This research is aimed at knowing how the implementation of STAD basedlLesson study on algebra subject is. This is a descriptive qualitative research which was done in three cycles consisting of “plan, do, and see” action in each of the cycles. The research subject was the third semester students of Mathematic departement. Based on the observation result done by the research observers, it was found that the implementation of STAD based Lesson Study enabled the lecturer and the students to learn cooperatively in the teaching and learning process on Algebra subject.